Emerging avalanche field-effect transistors based on two-dimensional semiconductor materials and their sensory applications - Elahi, Ehsan; Khan, Muhammad Farooq; Aziz, Jamal; Ahsan, Umer; Chauhan, Payal; Assiri, Mohammed A; Sarkar, Kalyan Jyoti; Asgher, Umer; Sofer, Zdenek (Journal of materials chemistry. C, Materials for optical and electronic devices, 2025)
Recently, two-dimensional (2D) layered semiconductors have been the subject of promising research work due to their intriguing physical and chemical characteristics. In electronic nano-devices, impact ionization is a viable condition to investigate or probe the level of sensitivity upon the application of external stimuli. However, avalanche field-effect transistors (FETs) have emerged as promising candidates for a wide range of sophisticated applications, especially for sensing traits. In this review, we explore the incorporation of 2D materials into avalanche FETs, highlighting their auspicious properties such as high carrier mobility, variable band gaps, and atomic thickness, which provide significant advantages over typical materials. 2D materials significantly improve the sensitivity, speed, and power efficiency of avalanche FETs. This study also encompasses the advances in photo-, bio- and gas-sensing technologies, emphasizing their implications in contemporary applications such as optoelectronics, imaging, and environmental monitoring. Thus, our review provides a thorough investigation of material attributes, device architecture, and prospective applications by establishing avalanche FETs with 2D materials as the keystone in power and rectifying applications. 2D heterostructure-based avalanche FET's enable efficient photo/gas/biomolecule sensing via enhanced carrier dynamics and tunable band alignments under forward/reverse bias.